Sodium butyrate enhances growth performance and intestinal development in broilers - Lan, Ruixia; Li, Siqi; Chang, Qingqing; An, Lilong; Zhao, Zhihui (Czech Journal of Animal Science, 2020)
The aim of this study was to evaluate the effects of sodium butyrate (SB) on growth performance and development of digestive and immune organs in broilers. Dietary treatments had similar compositions but with 0%, 0.03%, 0.06%, and 0.12% SB substituted (weight/weight) for identical amounts of the basal diet. SB supplementation linearly increased (P < 0.05) average daily gain for each period, except for days 15-21. SB supplementation linearly increased (P < 0.05) the relative weight of proventriculus (day 7), gizzard (days 7 and 14), duodenum (days 21 and 28), jejunum (day 21), ileum (day 21), small intestine (day 21), rectum (day 14), pancreas (days 7 and 21), liver (days 21 and 28), and thymus (days 7, 14, and 21). SB supplementation linearly increased (P < 0.05) the relative length of duodenum (day 21), jejunum (days 14 and 21), ileum (days 14 and 21) and small intestine (days 14 and 21), caeca (day 21) and rectum (day 21), as well as it improved intestinal structure by increasing the villus height in jejunum and ileum, and increasing goblet cell counts in duodenum, jejunum, and ileum. Collectively, dietary SB supplementation improved the growth performance of broilers by improving the development and morphological structure of the broilers' intestinal organs.
Keywords: relative weight; relative length; digestive organs; immune organs; broiler